JURIDICAL REVIEW OF THE MERGER OF COMPENSATION CLAIMS IN TRAFFIC ACCIDENT CASES IN KUPANG CITY AND ITS INHIBITING FACTORS BASED ON ARTICLE 98 OF THE CRIMINAL CODE IN KUPANG CLASS 1A DISTRICT COURT - Lulu, Maher Juanrez; Masu, Renny Rebeka; Resopijani, A (Artemis Law Journal, 2023)
This thesis is entitled "Juridical Review of the Merger of Compensation Lawsuits in Traffic Accident Criminal Cases and its Obstacles Based on Article 98 of the Criminal Procedure Code at the Kupang District Court Class 1A". The regulation of the merger of compensation claims is regulated in general through the provisions in articles 98-101 of Law Number 8 of 1981 concerning the Criminal Procedure Code. Based on Article 98 of the Criminal Procedure Code, the filing of a compensation claim is submitted no later than before the public prosecutor files a criminal charge. The role of the public prosecutor in the incorporation of compensation itself is to convey the rights of the victim to claim compensation at once in the judicial process and if the victim wants a civil compensation claim then the prosecutor will incorporate it into the criminal charges at once with the highest charge limit. The title of this thesis is directed to examine and research two problem formulations, namely: (1) How is the implementation of the merger of compensation claims in traffic accident cases at the Class 1A District Court, and (2) What are the inhibiting factors in the implementation of the merger of compensation claims in traffic accident cases at the Class 1A Kupang District Court. Based on the two problem formulations, the purpose of writing this thesis is to find out the mechanism of combining compensation claims in traffic accident cases and to find out the inhibiting factors. From the results of the author's research, there are obstacles that cause victims of traffic accidents not to file a merger of compensation claims, including the lack of proper socialization of article 98 of the Criminal Procedure Code, the ignorance of victims regarding the merger of compensation claims, and the lack of explanation from the prosecutor and the court regarding the merger of compensation claims according to article 98 of the Criminal Procedure Code to victims. It is hoped that the merger of lawsuits based on Article 98 of the Criminal Procedure Code, which facilitates victims in obtaining legal certainty effectively and efficiently, can be implemented for the realization of justice based on fast, cheap and low cost justice